Cerebral cortical thickness and surface area in adolescent anorexia nervosa: Separate and joint analyses with a permutation‐based nonparametric method. Issue 4 (17th December 2020) - Myrvang, Anna D.; Vangberg, Torgil R.; Stedal, Kristin; Rø, Øyvind; Endestad, Tor; Rosenvinge, Jan H.; Aslaksen, Per M.
Abstract: Objective: Reduction in cerebral volume is often found in underweight patients with anorexia nervosa (AN), but few studies have investigated other morphological measures. Cortical thickness (CTh) and surface area (CSA), often used to produce the measure of cortical volume, are developmentally distinct measures that may be differentially affected in AN, particularly in the developing brain. In the present study, we investigated CTh and CSA both separately and jointly to gain further insight into structural alterations in adolescent AN patients. Method: Thirty female AN inpatients 12–18 years of age, and 27 age‐matched healthy controls (HC) underwent structural magnetic resonance imaging. Group differences in CTh and CSA were investigated separately and jointly with a permutation‐based nonparametric combination method (NPC) which may be more sensitive in detecting group differences compared to traditional volumetric methods. Results: Results showed significant reduction in in both CTh and CSA in several cortical regions in AN compared to HC and the reduction was related to BMI. Different results for the two morphological measures were found in a small number of cortical regions. The joint NPC analyses showed significant group differences across most of the cortical mantle. Discussion: Results from this study give novel insight to areal reduction in adolescent AN patients and indicate that both CTh and CSA reduction is related to BMI. The study is the first to use the NPC method to reveal large structural alterations covering most of the brain in adolescent AN. Abstract :